2014 IEEE Fourth International Conference on Consumer Electronics Berlin (ICCE-Berlin) 2014
DOI: 10.1109/icce-berlin.2014.7034265
|View full text |Cite
|
Sign up to set email alerts
|

Underwater image quality enhancement through composition of dual-intensity images and Rayleigh-stretching

Abstract: The quality of underwater image is poor due to the properties of water and its impurities. The properties of water cause attenuation of light travels through the water medium, resulting in low contrast, blur, inhomogeneous lighting, and color diminishing of the underwater images. This paper proposes a method of enhancing the quality of underwater image. The proposed method consists of two stages. At the first stage, the contrast correction technique is applied to the image, where the image is applied with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 18 publications
0
32
0
Order By: Relevance
“…The results are illustrated with images of fishes and marine flora captured in the foreground. The HSV color space has been also used more recently in a twostage method (Ghani et al, 2014), for enhancing of coral images. First, the contrast correction technique is applied to the image with a modified Von Kries hypothesis and stretching it into two different intensity images at the average value with respect to Rayleigh distribution.…”
Section: Related Workmentioning
confidence: 99%
“…The results are illustrated with images of fishes and marine flora captured in the foreground. The HSV color space has been also used more recently in a twostage method (Ghani et al, 2014), for enhancing of coral images. First, the contrast correction technique is applied to the image with a modified Von Kries hypothesis and stretching it into two different intensity images at the average value with respect to Rayleigh distribution.…”
Section: Related Workmentioning
confidence: 99%
“…In Schoening et al (2012a) it was for instance shown, how the object distance to the centroid of the illumination cone influences the observers decision. A variety of algorithms have been developed to enhance underwater images by (a) dehazing the image (Trucco and Olmos-Antillon, 2006;Ancuti et al, 2012;Chiang and Chen, 2012), (b) compensating non-uniform illumination (Eustice et al, 2002;Singh et al, 2007;Schoening et al, 2012b;Bryson et al, 2015) and (c) increasing the image contrast and correcting the color shift (Zuiderveld, 1994;Eustice et al, 2002;Chambah et al, 2003;Trucco and Olmos-Antillon, 2006;Singh et al, 2007;Petit et al, 2009;Iqbal et al, 2010;Ancuti et al, 2012;Chiang and Chen, 2012;Schoening et al, 2012b;Abdul Ghani and Mat Isa, 2014;Bryson et al, 2015). Although in the last years new methods have been proposed to compare and rank the quality of different algorithms (Osterloff et al, 2014;Panetta et al, 2015;Yang and Sowmya, 2015), the selection of the best algorithm can be challenging.…”
Section: Introductionmentioning
confidence: 99%
“…The scattering of light is wavelength dependent so for correction of nonuniform illumination each color component (R, G, B) should be processed separately. While providing solution for nonuniform illumination, the method assumes that the underwater images are Rayleigh distributed [4][5][6]. Consider…”
Section: Introductionmentioning
confidence: 99%